The New Visibility of Religion and Its Impact on Populist Politics - Michael Hoelzl (Religions, 2020)
The marginalised research field of populism and religion has mainly focused on the positive aspects of how religion and populism can be combined with mutual benefits for both parties, whereas the critical potential and limitations that religion and theology pose to populist politics has often been overlooked. The following essay intends to contribute to the complex research area of religion and populism, by focusing on the negative side, that is, the incompatibilities of religion and theology with populism. It is suggested that the very nature of religious belief and theological convictions impose limits on their use in populist politics.